2017
DOI: 10.1097/pq9.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Improving Inpatient Asthma Management: The Implementation and Evaluation of a Pediatric Asthma Clinical Pathway

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Seven studies assessed the impact of CLDs or ICPs with discharge criteria on cost. Four studies13 15 18 19 reported statistically significant reductions in overall cost of admission. The observed improvement in cost ranged from a reduction of 3.3%15–40.4%19 compared with standard care.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies assessed the impact of CLDs or ICPs with discharge criteria on cost. Four studies13 15 18 19 reported statistically significant reductions in overall cost of admission. The observed improvement in cost ranged from a reduction of 3.3%15–40.4%19 compared with standard care.…”
Section: Resultsmentioning
confidence: 99%
“…LOS might be reduced because of various quality improvement initiatives (eg, discharging patients after every 3 hours albuterol treatments or respiratory therapist-driven protocols) and might not be related to IV magnesium use. 8,9 To this point, a recent study of a respiratory assessment score-matched cohort did not find any therapeutic benefit of IV magnesium with severe asthma exacerbation when receiving continuous albuterol therapy on a pediatric ward. 5 Perhaps future studies could explore estimating the outcome by performing comparative effectiveness studies between those with severe asthma exacerbation who did or did not receive IV magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…Trend analyses of outcomes suggest that increase in IV magnesium use was not associated with an increase in inpatient and ICU admission rate or with 7‐day all‐cause readmission rate, although LOS reduced. LOS might be reduced because of various quality improvement initiatives (eg, discharging patients after every 3 hours albuterol treatments or respiratory therapist–driven protocols) and might not be related to IV magnesium use 8,9 . To this point, a recent study of a respiratory assessment score–matched cohort did not find any therapeutic benefit of IV magnesium with severe asthma exacerbation when receiving continuous albuterol therapy on a pediatric ward 5 .…”
Section: Discussionmentioning
confidence: 99%
“…However, most protocols are focused on patients in general wards. [4][5][6][7] Traditionally, studies examining therapies for critical asthma have focused on specific therapies rather than protocols. 8,9 A retrospective review done previously at our institution found a wide variety of patient management strategies that were largely provider-dependent (unpublished data).…”
Section: Introductionmentioning
confidence: 99%